High Density Lipoprotein Reduces Blood Pressure and Protects Spontaneously Hypertensive Rats Against Myocardial Ischemia-Reperfusion Injury in an SR-BI Dependent Manner - Al-Jarallah, Aishah; Babiker, Fawzi (Frontiers in Cardiovascular Medicine, 2022)
Background: Hypertension is a key risk factor in the development of cardiovascular diseases. Elevation in blood pressure alters high density lipoprotein (HDL) function and composition. The exact role of HDL in cardiovascular complications observed in hypertension is however not clearly understood. HDL protected against myocardial ischemia/reperfusion (I/R) injury in normotensive rats. Nonetheless, it’s not clear if restoration of HDL function and/or composition protects against myocardial I/R injury in spontaneously hypertensive rats (SHR). Objectives: In this study we tested the effect of HDL treatment on I/R injury in Wistar Kyoto rats (WKY) and SHR and investigated the possible underlying mechanism(s). Methods: HDL (900 ng/kg/min) or vehicle were continuously administered to 11-week old WKY and SHR for one week (chronic treatment). Blood pressure was measured before and after treatment. Hearts were subjected to I/R injury using a modified Langendorff system. Another set of rats were treated with HDL administered at reperfusion (acute treatment) in the presence or absence of scavenger receptor class B type-I (SR-BI) blocking antibody. Cardiac hemodynamics were computed and cardiac enzymes release and infarct size were measured. Total cholesterol (TC) and HDL-cholesterol (HDL-C) were enzymatically assayed. Markers of autophagy and inflammation were detected by immunoblotting and ELISA, respectively. Results: HDL treatment did not increase TC or HDL-C levels in SHR or WKY, yet it significantly (P<0.01) reduced systolic and diastolic blood pressure in SHR. Chronic and acute HDL treatment significantly (P<0.05) protected WKY and SHR against myocardial I/R injury. Chronic HDL treatment was significantly (P<0.05) more protective in SHR whereas acute HDL treatment induced significantly (P<0.05) greater protection in WKY. The extent of HDL induced protection was proportional to the expression levels of cardiac SR-BI and blockage of SR-BI completely abolished HDL mediated protection in SHR. Chronic HDL treatment significantly (P<0.05) reduced markers of autophagy and inflammation including in hypertensive rats. Conclusions: We demonstrate a novel hypotensive and a cardioprotective effect of HDL against myocardial I/R injury in SHR, the magnitude is directly related to the expression levels of cardiac SR-BI. Mechanistically, chronic HDL treatment protected SHR hearts by reducing autophagy and inflammation.